Tingkat Penerangan dan Jarak Membaca Meningkatkan Kejadian Rabun Jauh (Miopia) pada Remaja - Khusni Karim; Ihsan Taufiq (Jurnal Kesehatan Metro Sai Wawai, 2017)
Background: WHO data in 2004 showed an incidence of 10% of 66 million school-age children suffering from refractive disorders, namely myopia. The peak of myopia is in adolescence at the high school level (16-18 years). In 2012 there were 226 cases consisting of 40 old cases and 186 new cases. Purpose: this study aims to determine the relationship of the level of illumination with reading distance with the incidence of myopia in SMA Negeri 03 Kotabumi, Kotabumi Selatan District. Methods: Research design analytic correlation with cross sectional method. The population in this study were all students in SMA Negeri 03 Kotabumi, Kotabumi Selatan District with a total sample of 85 people. Data is taken by quota sampling technique by accidental sampling. The variables analyzed were the level of illumination and reading distance, and the incidence of myopia by bivariate analysis using the chi square test. Results: The results showed that 45.9% had myopia and 54.1% had no myopia. Chi square test results show there is a relationship between the level of illumination with the incidence of myopia (p = 0.010; α = 0.05) and there is a relationship between reading distance and the incidence of myopia (p = 0,000; α = 0.05). Conclusion: Factors of light level and reading distance are associated with an increase in the incidence of myopia in adolescents. Efforts to reduce myopia by reading in a bright place and an ideal reading distance ( 30 cm).